2015
DOI: 10.1002/asia.201500560
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Properties, and Packing Structures of Corannulene‐Based π‐Systems Containing Heptagons

Abstract: Introduction of heptagons into hexagonal carbon lattices can generate negatively curved polycyclic aromatic hydrocarbons, which are of significant interest in the field of exotic molecular nanocarbons. We have successfully synthesized and characterized corannulene-based π-systems containing heptagons (4 and 5) as new negatively curved polycyclic aromatic hydrocarbons as well as possible intermediates in the synthesis of warped nanographene 1. The formation of 4 and 5 represents the first example for which a he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 40 publications
0
40
0
2
Order By: Relevance
“…An oxidative closure of five seven‐membered rings around a corannulene core yields the large asymmetric saddle‐shaped PAHs 196 a – c , as reported by Itami, Scott, and co‐workers (Figure ) . The authors demonstrated two different oxidative coupling strategies to construct the curved skeleton of these compounds.…”
Section: Intramolecular Oxidative Aromatic Couplingmentioning
confidence: 61%
See 2 more Smart Citations
“…An oxidative closure of five seven‐membered rings around a corannulene core yields the large asymmetric saddle‐shaped PAHs 196 a – c , as reported by Itami, Scott, and co‐workers (Figure ) . The authors demonstrated two different oxidative coupling strategies to construct the curved skeleton of these compounds.…”
Section: Intramolecular Oxidative Aromatic Couplingmentioning
confidence: 61%
“…The authors demonstrated two different oxidative coupling strategies to construct the curved skeleton of these compounds. Oxidation of deca(4‐ tert ‐butylphenyl)corannulene with FeCl 3 afforded the product 196 a in 62 % yield, whereas penta(biphenyl)‐substituted corannulenes yielded the corresponding curved PAHs 196 b and 196 c upon treatment with DDQ/TfOH (40 and 50 % yield, respectively) . The ease of closure of the seven‐membered rings is noteworthy, since an analogous reaction failed for the model compound [6]helicene .…”
Section: Intramolecular Oxidative Aromatic Couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…9 The X-ray crystal structure confirmed the distortion caused by the odd-membered rings, drastically enhancing solubility in organic solvents. Comparison with a purely hexagonal nanographene shows that the distortion of the planar sheet affects its electronic and optical properties.…”
Section: Introductionmentioning
confidence: 81%
“…[1,[14][15][16][17][18][19][20][21][22][23] Due to their saddle-shaped skeletons,n egatively curved nanographenes exhibit relatively weak inter- molecular p-p interactions and good solubility in organic solvents;t hey also possess interesting nonlinear optical and electrochemical properties.R ecently,w er eported aw arped nanographene (WNG) with one five-membered ring and five seven-membered rings in the hexagonal lattice ( Figure 1b). [1,[14][15][16][17][18][19][20][21][22][23] Due to their saddle-shaped skeletons,n egatively curved nanographenes exhibit relatively weak inter- molecular p-p interactions and good solubility in organic solvents;t hey also possess interesting nonlinear optical and electrochemical properties.R ecently,w er eported aw arped nanographene (WNG) with one five-membered ring and five seven-membered rings in the hexagonal lattice ( Figure 1b).…”
mentioning
confidence: 99%